(p‐(Diphenylarsino)phenyl)diphenylphosphine as a Novel Template for Heterodinuclear Complexes. Issue 2 (14th December 2020) - Akioka, Ippei; Sumida, Akifumi; Urushizaki, Aya; Imoto, Hiroaki; Naka, Kensuke
Abstract: Phosphorus and arsenic have different coordination ability to Lewis acids, though they belong to 15 group. Utilizing the difference, we designed a novel ligand, ( p ‐(diphenylarsino)phenyl)diphenylphosphine, in which diphenylphosphine and diphenylarsine units are combined through a p ‐phenylene linker, as a template to arrange Lewis acids. The phosphorus atom exhibited superior coordination ability to the arsenic one. NMR studies revealed that BH3, AuCl, and PtCl2 were preferentially coordinated by the phosphorus atom. Sequential addition of these Lewis acids realized precise arrangement on the template ligand. Abstract : Template ligand. ( p ‐(Diphenylarsino)phenyl)diphenylphosphine, in which dipheylphosphine and diphenylarsine are combined through a p ‐phenylene linker, can work as a template ligand to precisely arrange Lewis acids by sequential addition. The phosphorus atom was preferentially coordinated to a Lewis acid over the arsenic one. It has been demonstrated that combination of phosphorus and arsenic is a versatile strategy to design templates for heterodinuclear complexes.